1989
DOI: 10.1007/bf00285178
|View full text |Cite
|
Sign up to set email alerts
|

Assignment of the gene(s) involved in the expression of the proliferation-related Ki-67 antigen to human chromosome 10

Abstract: The antigen recognized by the monoclonal antibody Ki-67 is a proliferation-related nucleolus-associated constituent used as a marker for cycling cells in tumor diagnosis. Antibody Ki-67 reacts with human proliferating cells, but not with hamster and mouse cells. Expression of the Ki-67 antigen was studied in a panel of human-rodent somatic cell hybrids. The results indicate that a gene involved in the expression of the antigen is located on chromosome 10.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0
3

Year Published

1991
1991
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(65 citation statements)
references
References 13 publications
2
56
0
3
Order By: Relevance
“…Only AA/E7 showed suprabasal epithelial layers consisting of highly keratinized and atypical cells. Ki67, a marker to determine the growth fraction of a given cell population (Schonk et al, 1989) was observed in single cells within the lower, and interestingly, also the upper (keratinizing) part of the AA/E7 raft epithelium, as well as in single cells of the E6/E7 raft epithelium (Figure 4b). Although differentiation-associated cytokeratin 10 (K10), was found in the majority of suprabasal cells within the AA/E7 culture, the E6/E7 culture was devoid of any K10 staining ( Figure 4b).…”
Section: Resultsmentioning
confidence: 96%
“…Only AA/E7 showed suprabasal epithelial layers consisting of highly keratinized and atypical cells. Ki67, a marker to determine the growth fraction of a given cell population (Schonk et al, 1989) was observed in single cells within the lower, and interestingly, also the upper (keratinizing) part of the AA/E7 raft epithelium, as well as in single cells of the E6/E7 raft epithelium (Figure 4b). Although differentiation-associated cytokeratin 10 (K10), was found in the majority of suprabasal cells within the AA/E7 culture, the E6/E7 culture was devoid of any K10 staining ( Figure 4b).…”
Section: Resultsmentioning
confidence: 96%
“…Ki67 is a commonly used marker in proliferating cells, yet surprisingly little is known about its function. The Ki67 gene is located on the human chromosome 10 and mouse chromosome 7 (Schonk et al, 1989;Fonatsch et al, 1991). Two alternatively spliced mRNA species encode two isoforms of the protein: a larger isoform (359 kD) and a smaller isoform (320 kD) (Gerdes et al, 1983;Schluter et al, 1993).…”
Section: Implications Of Ki67 Presence Beyond Cell Birthmentioning
confidence: 99%
“…MIB-1 is an antibody against Ki-67, an excellent cellular marker of proliferation. 27 However, no relationship was observed between Wnt9A and MIB-1 expression levels. Accordingly, Wnt9a is unlikely to affect cell proliferation.…”
Section: Discussionmentioning
confidence: 98%